Authentic Leadership and Task Performance via Psychological Capital: The Moderated Mediation Role of Performance Pressure - Jang, Eunmi (Frontiers in Psychology, 2022)
Authentic leadership has received significant academic attention. It is now imperative to understand how authentic leadership’s effectiveness varies in different situations or conditions, which is vital to re-establishing it as an independent leadership theory. To this end, this study aims to verify the positive influence of authentic leadership on the task performance of members within an organization. Further, it seeks to confirm the situations that moderate the relationship between authentic leadership and task performance. Specifically, the mediating mechanism of psychological capital in this relationship, the moderating effect of performance pressure on the relationship between authentic leadership and psychological capital, and the moderated mediating effect are demonstrated. This study used a time-lagged survey to test the hypotheses; two online surveys were staggered by one month and completed by 485 participants in South Korea. The empirical analysis confirmed all the proposed hypotheses. First, authentic leadership was positively related to task performance. Second, psychological capital had a mediating effect on the relationship between authentic leadership and task performance. Third, task performance pressure was negatively related to the relationship between authentic leadership and psychological capital. Specifically, the strength of the indirect effect increased as the employee performance pressure decreased. Based on these results, various theoretical and practical implications are suggested for the extended application of the authentic leadership theory in organizations and future research directions are proposed.